Indian power policy, Enron and the BoP - Srinivasan, Kannan (1996)
"The Enron deal has given investors an unrealistic expectation of the returns they can receive under the government's power policy. Glimpses provided by documents of how the government decided on Enron show it to have been fully aware of the damage this decision would cause. The Amended Power Purchase Agreement negotiated by the committee appointed by the Shiv-Sena-BJP government is even worse for the interests of Maharashtra than the Congress original of 1994. The balance of payments consequences of fuel imports for naphtha and fuel oil-based power plants will be ruinous"
Keywords: Power industry - India - Maharashtra; Energy Industries